Effects of Cu2+ on stability and composition of water soluble ternary polyacrylic acid-Cu2+-protein complexes against radiation damage - Mastafaev, M. I.; Sara, A. S.; Erkol, A. Y.; Baylken, S.; Diner, B.; Sezer, E. (Springer Science and Business Media LLC, 1996)
The formation of water soluble ternary complexes of polyacrylic acid (PAA) and bovine serum albumin (BSA) in the presence of divalent copper ions was investigated at the neutral pH. Aqueous solutions of PAA, BSA, and their mixture (PAA-BSA, PAA-Cu2+-BSA) have been irradiated with 60Co γ-rays and the changes occurred have been measured by high performance liquid chromatography (HPLC) and spectrophotometry. Addition of Cu2+ ions to PAA-BSA mixture have been shown to protect the PAA and BSA components of ternary PAA-Cu2+-BSA complexes against radiation damage. A structural model of ternary polycomplexes was proposed and the mechanism of observed protection effect was discussed.